Diversification is decoupled from biome fidelity: Acacia – a case study. (26th December 2019) - Dale, Esther E.; Larcombe, Matthew J.; Lee, William G.; Higgins, Steven I.
Abstract: Aim: To investigate species and clade biome occupancy patterns of Australian Acacia to test for within‐biome diversification, which indicate biome conservatism. Location: Australia. Taxon: Acacia (Fabaceae). Methods: Species distributions were predicted for 481 Australian Acacia using the Thornley Transport Resistance Species Distribution Model and mapped across four biome typologies. Within Acacia 19 clades were identified. The number of biomes occupied and niche size was quantified for every species and clade using the range area projected by the distribution model. Relationships between clade species richness, niche size and biomes occupied were tested using phylogenetic least squares regression models. Results: Only 9% of the Acacia 481 species and no clades were biome specialists. There were most specialist taxa in the Crisp Biome classification (8.7%), followed by WWF Biomes (6.2%), González–Orozco Biomes (5.0%) then Functional Biomes (1.2%). On average Acacia species occupied four WWF Biomes, seven Functional Biomes, three Crisp Biomes and three González–Orozco Biomes (out of 7, 13, 5 or 6 biomes respectively). Clades were also distributed across multiple biomes (2–13) with a significant positive relationship between clade species richness and the number of biomes occupied for all biome typologies. Species richness had positive linear relationships with biome area for all biome concepts except the González–Orozco Biomes. Larger clades had larger niche sizes. Main conclusions: Acacia diversification occurred across biome boundaries and was not associated with biome specialization. Species and clades mainly occurred in multiple biomes, and there were typically few biome specialists. Diversification in Acacia appears to be decoupled from biome conservatism, associated with expanding niche size across biome boundaries. Major ecological–environmental units such as biomes may constrain adaptive radiation processes via biome conservatism in many groups, but this study leads us to hypothesize that for some lineages biome boundaries are permeable.